Hydrolytically Degradable Hyperbranched PEG‐Polyester Adhesive with Low Swelling and Robust Mechanical Properties. Issue 15 (8th September 2015) - Zhang, Hong; Zhao, Tianyu; Duffy, Patrick; Dong, Yixiao; Annaidh, Aisling Ní; O'Cearbhaill, Eoin; Wang, Wenxin
Abstract : Photocrosslinkable and water soluble hyperbranched PEG‐polyester polymers (HPEGDA) have been developed as robust degradable adhesives. The HPEGDA polymers have been synthesized from controlled homopolymerization of poly(ethylene glycol) diacrylate (PEGDA700 ) via in situ deactivation enhanced atom transfer radical polymerization (DE‐ATRP). By introducing a high initiator‐to‐monomer ratio, the obtained HPEGDA polymer is composed of extremely short carbon–carbon backbones interconnected together by the long PEG chains as well as pendent photocrosslinkable acrylate moieties. Due to the extremely short C–C backbone, the long PEG chains can therefore be seen as the main chain, thus, HPEGDA polymers behave more like polyester which is a category of polymers that contain the ester functional group in their main chain. Photo‐cured HPEGDA can be readily adhered to tissue forming a patch with robust mechanical and adhesive strengths. The degradation profile by hydrolysis of polyester blocks as well as a significantly low swelling ratio of HPEGDA gels in an aqueous environment allow them to have great potential for sealing and repair of internal tissue. Furthermore, HPEGDA gels appear to have minor significant cytotoxicity in vitro. These unique properties indicate that the reported HPEGDA polymers are well poised for the development of adhesive tissue engineering matrixes, wound dressings, and sealants. Abstract : A range of photocrosslinkable and water soluble hyperbranched PEG‐polyester polymers (HPEGDA) have been developed as robust degradable adhesives. By introducing a high initiator‐to‐monomer ratio, the obtained HPEGDA polymer is composed of extremely short carbon–carbon backbones interconnected together by the long PEG chains as well as pendent photocrosslinkable acrylate moieties. Due to the extremely short C–C backbone, the long PEG chains can therefore be seen as the main chain, thus, HPEGDA polymers behave more like polyester. Photo‐cured HPEGDA can be readily adhered to tissue forming a patch with robust mechanical and adhesive strengths.